Women, Youth, and Minorities and the Case of the Missing Productivity - Burggraf, Shirley P. (American Economic Review, 1984)
Women, youth, and minorities are frequently cited as an almost one-word explanation for declining productivity growth in the U.S. labor force as measured at the macro level. While some economists have proposed theories to account for productivity slowdown which emphasize such things as declining capital-labor ratio (J. R. Norsworthy, Michael Harper, and Kent Kunze, 1979); energy constraint (Edward Hudson and Dale Jorgenson, 1978); and macro instability (Richard Nelson, 1980; Michael Mohr, 1980), many analysts have cited the changing composition of the labor force as a significant contributing factor. (See, for example, Edward Denison, 1979; Norsworthy et al.; Frank Gollop and Jorgenson, 1980.) These assertions are tantamount to suggesting that admitting certain groups into the labor force necessarily lowers productivity and should not go unchallenged for several reasons. Inferring negative productivity coefficients to particular groups is likely to reinforce statistical discrimination whereby employers use perceived characteristics of groups as information shortcuts for making decisions about individuals (Edmund Phelps, 1972). It also has considerable implication for future U.S. productivity trends as the demographic composition of the labor force continues to change, and for formulating appropriate labor policies. This paper examines labor market trends and productivity measurement methodology as it pertains to labor force composition, and concludes that whether women, youth, and minorities have contributed significantly to the decline in productivity growth, and are likely to do so in the future, depends on how productivity is defined and measured. Current definitions of productivity are essentially based on micro concepts. I argue that they may be misleading indicators of trends in economic efficiency at the macro level, especially under the conditions of social change and labor-supply growth which characterized the 1970's.